Pengaruh Medium yang Tercemar Organoklorin (Endosulfan) terhadap Kandungan Agar dan Morfologi Thallus Gracilaria verrucosa [Effect Of Organochlorines (Endosulfan) Contaminated Medium On Content Of Gelatin and Thallus Morphology Gracilaria verrucosa] - Moch. Amin Alamsjah; Handini Fidya Riswanti; Agustono Agustono (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Gracilaria verrucosa seaweed is one of the high economic value because its potential as raw with the good content of more agarose than agaropektin so that it can produce gelatin to form strong and solid gelatin. The content range is from 12-48% depending on the class species Rhodophyceaea. Organochlorine residues (Endosulfan) come down to sea by the use of Organochlorine continuously, finally settles on the ground and carried by the flow of rain. Organochlorine residues (Endosulfan) excess in aquatic may influence biota so that can degrade and change the content that Thallus morphology on Gracilaria verrucosa. This research aims to determine the content of that reduction and morphological changes of Gracilaria verrucosa thallus on organochlorine contaminated medium (Endosulfan). This research method s experimental, while the design of the study is a Rancangan Acak Lengkap (RAL) with 5 treatments and 4 replications. The main parameters in this research that content of gelatin and thallus morphology Gracilaria verrucosa, while supporting parameters in this study consisted of: water quality medium. The results showed that the organochlorine contaminated medium (Endosulfan) significantly influenced (p <0.05) of the gelatin content. Ingredients that are highest in treatment A (41.2%). Content that is second highest on treatments B (35.55%). Ingredients that are the third highest in treatment C (22.02%), followed by treatment D (16.72%) and treatment E (13%) showed the lowest gelatin. Each treatment showed significantly different between treatments. Thallus morphology Observations show differences in the thickness of the thallus epidermis such as the dose of pollutant. The greater the dose of organochlorines (Endosulfan) given the Thallus epidermis G. verrucosa diminution.